If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m(m + 3) + 2(m + 3) = 0 Reorder the terms: -3m(3 + m) + 2(m + 3) = 0 (3 * -3m + m * -3m) + 2(m + 3) = 0 (-9m + -3m2) + 2(m + 3) = 0 Reorder the terms: -9m + -3m2 + 2(3 + m) = 0 -9m + -3m2 + (3 * 2 + m * 2) = 0 -9m + -3m2 + (6 + 2m) = 0 Reorder the terms: 6 + -9m + 2m + -3m2 = 0 Combine like terms: -9m + 2m = -7m 6 + -7m + -3m2 = 0 Solving 6 + -7m + -3m2 = 0 Solving for variable 'm'. Factor a trinomial. (2 + -3m)(3 + m) = 0Subproblem 1
Set the factor '(2 + -3m)' equal to zero and attempt to solve: Simplifying 2 + -3m = 0 Solving 2 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3m = 0 + -2 -3m = 0 + -2 Combine like terms: 0 + -2 = -2 -3m = -2 Divide each side by '-3'. m = 0.6666666667 Simplifying m = 0.6666666667Subproblem 2
Set the factor '(3 + m)' equal to zero and attempt to solve: Simplifying 3 + m = 0 Solving 3 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + m = 0 + -3 m = 0 + -3 Combine like terms: 0 + -3 = -3 m = -3 Simplifying m = -3Solution
m = {0.6666666667, -3}
| 3x-4y=-4 | | -x^2=5x | | 4x^2+16=16 | | Y=(x+3)(x^2+8x+15) | | 20x^3-12x=0 | | 56o=86 | | -3(3y+5)-11=-6(y+6)+3y | | 101=(2x+6) | | 4x^2+20x-8=0 | | 5a-6c=n | | 10x+5=2x-9 | | 82=(5x-40) | | -15c+4a=m | | 0=8x^2-14x | | 2g+12=3G-1 | | 5+-3a=n | | 61=(94x-20) | | 15x-120=6x-90 | | 2y-8x=-18 | | -.30(x-9)=-.50 | | 7x-(2x+7)=8x-46 | | 8+8=a | | (3x+18)(3x+18)=36 | | 4-2a=m | | 3x^2-12x+2x-8= | | 8x-(4x+6)=10 | | (3n+2)=0 | | 2(7x-1)=29 | | x^2+14=9x | | -3x+5=-3 | | -75y+.25=.50 | | 4x+2=21 |